A comprehensive look of poly(ADP-ribose) polymerase inhibition strategies and future directions for cancer therapy. (January 2017) - Kumar, Chandan; Rani, Nidhi; Velan Lakshmi, Palanisamy Thanga; Arunachalam, Annamalai
The finding of promising drugs represents a huge challenge in cancer therapeutics, therefore it is important to seek out novel approaches and elucidate essential cellular processes in order to identify potential drug targets. Studies on DNA repair pathway suggested that an enzyme, PARP, which plays a significant role in DNA repair responses, could be targeted in cancer therapy. Hence, the efficacy of PARP inhibitors in cancer therapy has been investigated and has progressed from the laboratory to clinics, with olaparib having already been approved by the US FDA for ovarian cancer treatment. Here, we have discussed the development of PARP inhibitors, strategies to improve their selectivity and efficacy, including innovative combinational and synthetic lethality approaches to identify effective PARP inhibitors in cancer treatment.